Pengaruh Penambahan Macam Starter Pada Proses Pengomposan Limbah Organik : The Effect of Adding Types of Starters to the Organic Waste Composting Process - Sa'adah, Tatuk Tojibatus; Herawati, Jajuk; Susanti, Ria Endah (Journal of Applied Plant Technology, 2022)
Composting is a method of converting organic materials into simpler materials using microbial activity. The aim of the study was to determine the effect of adding different types of starter to the composting process of vegetable waste and garden waste. This study used a factorial completely randomized design, consisting of two factors. Factor 1: Type of Starter Material (S), consists of 3 levels S0: No starter, S1: EM4 (Effective Microorganisms) 20% + Urea 200 gr ; S2: MOL (POC Water Hyacinth) 20% + Urea 200 gr. Factor II: types of organic waste, L1: organic vegetable waste, and L2: Gardening organic waste. The results of the study on the treatment of starter types and types of organic waste in the composting process can be concluded as follows: Treatment of vegetable organic waste with starter types and types of waste, the final pH of composting in this study ranged from 7.67-7.94 with temperatures ranging from 27.0 – 28.3 0C, and the occurrence of volume shrinkage ranging from 61.48% to 95 has a C/N ratio of 14.24. - 18.75